Minimise Weight, Increase Retention: Hollow Denture - A Case Report - Rai, A.; Kharel, B.; Suwal, P.; Parajuli, P. K.; Limbu, I.; Basnet, B. B. (Journal of Nepalese Prosthodontic Society, 2021)
The increased inter-ridge space due to resorption of residual ridge and long upper lip length makes the prosthetic rehabilitation of such patient a great challenge for a prosthodontist. Retention and stability of complete denture in cases of residual ridge resorption is usually reduced because of minimised denture bearing area. The maxillary denture fabricated in such patients are bulky in nature which further compromise its retention. So, in this case report a simplified technique is described for construction of hollow maxillary denture which being light in weight further improves denture retention.